Effect of Angle Shear Connectors on the Behavior of Composite Concrete Steel Flexural Members Under Negative Moment - M. Al-Khekany, Alaa; S. Al-Yassri, Labeeb; A. Al-Ramahee, Munaf; Abdul-Abbas, Saeed (International Journal of Engineering and Technology, 2018)
This research presents an experimental program to study the effect of using angle shear connectors instead of the headed stud on the flexural behavior of composite beams under negative bending moment (NBM). Both the angle and headed stud shear connectors used in this study have the same cross-sectional area. Five composite beams were casted and tested using three-point load configuration to ensure the NBM effect. Different parameters were included in this study such as the type of shear connector, bond interaction (partial and complete bond interaction) and arrangement of angle shear connectors. Two proposals method were suggested for angle setting in this study to investigate the structural behavior of the composite section. It has been found that, in the case of single angle shear connectors, the ultimate strength decreased by 4.12% compared with samples with the headed stud shear connectors. The direction of the angle setting has been shown to affect the flexural behavior of the composite section.
Keywords: Angle shear connectors; Bond interaction; Composite section; Negative moment; Shear connectors.